Neutron Interferometry at the National Institute of Standards and Technology. (9th March 2015) - Pushin, D. A.; Huber, M. G.; Arif, M.; Shahi, C. B.; Nsofini, J.; Wood, C. J.; Sarenac, D.; Cory, D. G.
Abstract : Neutron interferometry has proved to be a very precise technique for measuring the quantum mechanical phase of a neutron caused by a potential energy difference between two spatially separated neutron paths inside interferometer. The path length inside the interferometer can be many centimeters (and many centimeters apart) making it very practical to study a variety of samples, fields, potentials, and other macroscopic medium and quantum effects. The precision of neutron interferometry comes at a cost; neutron interferometers are very susceptible to environmental noise that is typically mitigated with large, active isolated enclosures. With recent advances in quantum information processing especially quantum error correction (QEC) codes we were able to demonstrate a neutron interferometer that is insensitive to vibrational noise. A facility at NIST's Center for Neutron Research (NCNR) has just been commissioned with higher neutron flux than the NCNR's older interferometer setup. This new facility is based on QEC neutron interferometer, thus improving the accessibility of neutron interferometry to the greater scientific community and expanding its applications to quantum computing, gravity, and material research.